Transcriptional Patterning of the Ventricular Cardiac Conduction System. Issue 3 (17th July 2020) - Burnicka-Turek, Ozanna; Broman, Michael T.; Steimle, Jeffrey D.; Boukens, Bastiaan J.; Petrenko, Nataliya B.; Ikegami, Kohta; Nadadur, Rangarajan D.; Qiao, Yun; Arnolds, David E.; Yang, Xinan H.; Patel, Vickas V.; Nobrega, Marcelo A.; et al.
Abstract : Rationale: The heartbeat is organized by the cardiac conduction system (CCS), a specialized network of cardiomyocytes. Patterning of the CCS into atrial node versus ventricular conduction system (VCS) components with distinct physiology is essential for the normal heartbeat. Distinct node versus VCS physiology has been recognized for more than a century, but the molecular basis of this regional patterning is not well understood. Objective: To study the genetic and genomic mechanisms underlying node versus VCS distinction and investigate rhythm consequences of failed VCS patterning. Methods and Results: Using mouse genetics, we found that the balance between T-box transcriptional activator, Tbx5, and T-box transcriptional repressor, Tbx3, determined the molecular and functional output of VCS myocytes. Adult VCS-specific removal of Tbx5 or overexpression of Tbx3 re-patterned the fast VCS into slow, nodal-like cells based on molecular and functional criteria. In these cases, gene expression profiling showed diminished expression of genes required for VCS-specific fast conduction but maintenance of expression of genes required for nodal slow conduction physiology. Action potentials of Tbx5 -deficient VCS myocytes adopted nodal-specific characteristics, including increased action potential duration and cellular automaticity. Removal of Tbx5 in vivo precipitated inappropriate depolarizations in the atrioventricular (His)-bundle associated with lethal ventricular arrhythmias. TBX5 bound and directly activated cis -regulatory elements at fast conduction channel genes required for fast physiological characteristics of the VCS action potential, defining the identity of the adult VCS. Conclusions: The CCS is patterned entirely as a slow, nodal ground state, with a T-box dependent, physiologically dominant, fast conduction network driven specifically in the VCS. Disruption of the fast VCS gene regulatory network allowed nodal physiology to emerge, providing a plausible molecular mechanism for some lethal ventricular arrhythmias. Abstract : Supplemental Digital Content is available in the text.